Lymphatic Vessel Invasion in Routine Pathology Reports of Papillary Thyroid Cancer - Chiapponi, Costanza; Alakus, Hakan; Schmidt, Matthias; Faust, Michael; Bruns, Christiane J.; Büttner, Reinhard; Eich, Marie-Lisa; Schultheis, Anne M. (Frontiers in Medicine, 2022)
Purpose It is not mandatory to report lymphatic vessel invasion in pathology reports of papillary thyroid cancer (PTC) according to the current Union for International Cancer Control (UICC) TNM (tumor, nodes, and metastases) classification. However, there is some evidence for its correlation with lymph node metastasis (LNM) and prognosis. The aim of this study was to explore the clinical implication of lymphatic vessel invasion documentation of PTC because pathology reports play a pivotal role in postsurgical clinical decision-making in endocrine tumor boards. Methods Patients undergoing postoperative radioiodine treatment for PTC at the University Hospital of Cologne, Germany between December 2015 and March 2020 were identified. Pathology reports were screened for documentation of lymphatic vessel invasion. Demographics and clinicopathologic data of patients documented, including lymphatic vessel invasion and lymph nodal involvement were analyzed. Results A total of 578 patients were identified and included. Lymphatic vessel invasion was reported in pathology reports of 366 (63.3%) and omitted in 112 (36.7%) patients. Positive lymphatic vessel invasion (L1) was diagnosed in 67 (18.3%) of 366 patients and was documented as absent (L0) in 299 (81.7%) patients. Lymph nodal (N) status was positive (N+) in 126 (45.6%) and negative (N0) in 150 (54.3%) of these patients. In 54 (80.6%) L1 cases N+ status and in 137 (65.6%) L0 cases N0 status was diagnosed. In 13 (19.4%) cases with L1 status, there were no LNMs (L1 N0). In total, 72 (34.4%) patients had LNM despite L0 status (L0 N+). The sensitivity and specificity of LVI reporting for LNM were 0.42 and 0.91, respectively. Conclusion In routine pathology reports of PTC used for indication to postoperative radioiodine treatment by a German endocrine tumor board, lymphatic vessel invasion was found to be reported inconsistently and mostly as L0. L1 diagnoses, however, reliably correlated with reported LNM and might, thus, be relevant for clinical decision-making. For this reason, we advocate for standardized pathologic reassessment of lymphatic vessel invasion, in particular for cases where lymph nodes are not included in the pathologic specimen and if L0 is documented.